2009
DOI: 10.1089/acm.2008.0630
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Management with Interactive Computer Technology and Nutrition: Two Case Reports

Abstract: We present two cases of obstructive sleep apnea (OSA) in which one of the subjects was managed with virtual scanning, which is a computer interactive diagnostic and therapeutic technology, and the other was treated with nutrition. We propose an oxidative stress concept as the biochemical basis of the two management options. It is important to consider the validity of virtual scanning Technology (which can be used to manage sleep apnea noninvasively) and to determine whether oxidative stress is the biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Recent published papers by the author illustrate how SVS can be used to determine the complex range of pathological coordinates in patients with diabetes, diabetic comorbidities, cardiovascular disease [15], migraine [16], Raynaud's phenomenon [17], Alzheimer's disease [18], etc; and how SLT can be used with therapeutic effect in cases of diabetic circulatory issues (ulcers), high blood pressure, abnormally low cytokines levels [19], migraine [20], headache, depression, sleeping disorders [21], etc.…”
Section: Resultsmentioning
confidence: 99%
“…Recent published papers by the author illustrate how SVS can be used to determine the complex range of pathological coordinates in patients with diabetes, diabetic comorbidities, cardiovascular disease [15], migraine [16], Raynaud's phenomenon [17], Alzheimer's disease [18], etc; and how SLT can be used with therapeutic effect in cases of diabetic circulatory issues (ulcers), high blood pressure, abnormally low cytokines levels [19], migraine [20], headache, depression, sleeping disorders [21], etc.…”
Section: Resultsmentioning
confidence: 99%
“…The patient attended a diabetes research screening clinic where WBV was tested and identified to be in the abnormal low range. Based on the WBV result, patient resorted to nutrition and physical activities as alternative therapeutic measures [27]. …”
Section: Discussionmentioning
confidence: 99%
“…is able to treat a wide range of ailments [25]. VSLT has been used to successfully treat a range of disorders including sleep disorders [53], breathing disorders, migraine w/o aura [54], circulatory problems, developmental dyslexia [55,56], etc. Our experience largely supports the claims by Vysochin, in an unpublished article prepared for the Russian parliament THE DUMA [25], that the technique is circa 93% effective.…”
Section: Initial Indications Are That Virtual Scanning Light Therapy mentioning
confidence: 99%